The Influence of Halal Lifestyle on the Development of Islamic Medical Tourism with Islamic Branding as a Moderating Factor in Islamic Hospitals in Indonesia - Solikhah, Puji; Faozi, Mohamad (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Medical tourism is a continuously growing global industry, with Indonesia showing considerable potential, especially within the specialized niche of Islamic Medical Tourism (IMT). The increasing prominence of the post-pandemic halal lifestyle has amplified the demand among Muslim communities for healthcare services that strictly adhere to Islamic principles. This research investigates the impact of the Halal Lifestyle on Islamic Medical Tourism and examines the moderating role of Islamic Branding within the context of Islamic Hospitals in Indonesia. A quantitative research design was employed, collecting data through an online survey from 100 respondents who had previously utilized services at Islamic Hospitals. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal a significant positive influence of Halal Lifestyle on Islamic Medical Tourism ($p < 0.001$). Furthermore, Islamic Branding demonstrated a direct, positive effect on IMT ($p = 0.004$). Crucially, however, the results indicate that Islamic Branding does not significantly moderate the relationship between Halal Lifestyle and Islamic Medical Tourism ($p = 0.216$). This research suggests that while the Muslim community's preference for a halal lifestyle is robust, Islamic branding alone is insufficient to enhance the attractiveness of medical tourism unless tangible improvements in physical facilities, service quality, and the professionalism of medical staff complement it. Theoretically, this research contributes to the literature on Muslim consumer behavior. In practice, it provides strategic recommendations for Islamic Hospitals to optimize their competitiveness in the medical tourism sector.